Europa Postmediaevalis 2018 : post-medieval pottery between (its) borders - Blažková, Gabriela, 1974-; Matějková, Kristýna, (Archaeopress Publishing Ltd, 2019)
This anthology is a collection of works from the Europa Postmediaevalis conference held in Prague in the spring of 2018. As the name of the conference suggests, the subject of interest is the Early Modern period (15th to 18th century) and the manner in which this relatively young discipline in the field of archaeology is approached in Europe.